Tau haploinsufficiency causes prenatal loss of dopaminergic neurons in the ventral tegmental area and reduction of transcription factor orthodenticle homeobox 2 expression. Issue 8 (19th September 2017) - Zheng, Meige; Jiao, Luyan; Tang, Xiaolu; Xiang, Xianhong; Wan, Xiaomei; Yan, Yan; Li, Xingjian; Zhang, Guofeng; Li, Yonglin; Jiang, Bin; Cai, Huaibin; Lin, Xian
ABSTRACT: Homozygous tau knockout (Mapt ‒ / ‒ ) mice develop age‐dependent dopaminergic (DA) neuronal loss in the substantia nigra (SN) and ventral tegmental area (VTA), supporting an important function of tau in maintaining the survival of midbrain dopaminergic neurons (mDANs) during aging. However, it remains to be determined whether the microtubule‐associated protein tau regulates the differentiation and survival of mDANs during embryonic developmental stages. Here, we show that tau haploinsufficiency in postnatal day 0 (P0) heterozygous (Mapt +/ ‒ ) pups, but not a complete loss of tau in the Mapt ‒ / ‒ littermates, led to a significant reduction of DA neurons in the VTA. This selective loss of DA neurons correlated with a similar reduction in orthodenticle homeobox 2 (Otx2), which is restricted to VTA neurons at the postmitotic stage and selectively controls the neurogenesis and survival of specific neuronal subtypes of VTA. Moreover, the prenatal developmental cell death in the Mapt +/ ‒ VTA specifically increased, and the expression of microtubule‐associated protein (MAP)‐1A was significantly up‐regulated in the P0 Mapt ‒ / ‒, but not the Mapt +/‒, pups. These results suggest that tau haploinsufficiency, without the compensation effect of MAP1A, induces reduction of Otx2 expression, increases prenatal cell death, and accordingly leads to selective loss of VTA DA neurons in the early postnatal stage. Our findings highlight the impact of tau haploinsufficiency on the survival of mDANs and indicate that tau may participate in midbrain development in a dose‐dependent way.—Zheng, M., Jiao, L., Tang, X., Xiang, X., Wan, X., Yan, Y., Li, X., Zhang, G., Li, Y., Jiang, B., Cai, H., Lin, X. Tau haploinsufficiency causes prenatal loss of dopaminergic neurons in the ventral tegmental area and reduction of transcription factor orthodenticle homeobox 2 expression. FASEB J . 31, 3349–3358 (2017). www.fasebj.org